(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
We consider the partial digest problem, which aims to find the set \(X={x_0, x_1,…,x_n}\) such that \(Δ X={ | x_j – x_i |, 0≤ i < j ≤ n}\) is equal to the input of the problem which is a multiset \(D={d_1, d_2,…, d_m}\). In bioinformatics, the lengths of DNA fragments represents the multiset \(D\), while the set of restriction site locations represents the set \(X={x_0, x_1,…, x_n}\). In this paper, we study experimentally the effect of increasing and decreasing the number of levels on the breadth-breadth algorithm which is the best practical algorithm for the partial digest problem. The experimental study shows that the running time of breadth-breadth method is not the minimum time. Also, we obtained the number of levels that is used in the breadth-breadth algorithm to reduce the running time.